2022
DOI: 10.1208/s12249-021-02187-4
|View full text |Cite
|
Sign up to set email alerts
|

Solid Dispersions of Gefitinib Prepared by Spray Drying with Improved Mucoadhesive and Drug Dissolution Properties

Abstract: Gefitinib is a tyrosine kinase inhibitor that is intended for oral administration yet suffers poor bioavailability along with undesirable side effects. To enhance its solubility and allow colon targeting, gefitinib (ZD) and blends of different ratios of polymers (ternary dispersion) were prepared in organic solution, and solid dispersions were generated employing the spray drying (SD) technique. The methylmethacrylate polymer Eudragit S 100 was incorporated for colon targeting; polyvinylpyrrolidone (PVP) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…However, after being in an alkaline medium (pH 6.8), the three multiparticulate systems showed a more porous structure. Similar studies were carried out by several authors [ 53 , 56 , 61 ]. Therefore, SEM images (pH 6.8) let us assume that the dissolution happens through pores that are generated by a combination of drug diffusion [ 56 ] and polymer swelling/eroding processes [ 53 ].…”
Section: Resultssupporting
confidence: 80%
“…However, after being in an alkaline medium (pH 6.8), the three multiparticulate systems showed a more porous structure. Similar studies were carried out by several authors [ 53 , 56 , 61 ]. Therefore, SEM images (pH 6.8) let us assume that the dissolution happens through pores that are generated by a combination of drug diffusion [ 56 ] and polymer swelling/eroding processes [ 53 ].…”
Section: Resultssupporting
confidence: 80%
“…The results of FTIR analysis showed that in the spectra of the produced microspheres, the secondary amine sharp peak present in the pure carvedilol disappeared and a broad peak at the same wavenumber range (around 3366.21 cm−1) was observed, which is indicative of formation of hydrogen bond (which is a physical bond) between the O-and NH groups of the drug and polymers 36 . This might be evidence indicating a breakdown in the crystalline structure of carvedilol, leading to the formation of the amorphous state within the microspheres.…”
Section: Discussionmentioning
confidence: 98%
“…36,37 We have investigated the effect of formulation on viability of Caco-2 cells and the results showed that the surfactant used in the solid dispersion formulation is devoid of any cytotoxic effect on Caco-2 cells which is in accordance to a previous report. 29 The improvement in the dissolution profile of cholecalciferol from DRHCap-SD can be attributed to the protection of the cholecalciferol in acidic SGF condition and this can also be associated with the reduction in particle size of the cholecalciferol and its possible amorphization of solid dispersion, enhanced wetting of the drug and the possible solubilization effect of the polymer or surfactant. The bulk properties of the developed solid dispersion and their physical mixture were evaluated and the results demonstrated that the flow properties were improved by formulation of solid dispersion.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated in the study that the surfactant used in the solid dispersion formulation is devoid of any cytotoxic effect on Caco-2 cells and the observations are in accordance to a previous study. 29…”
Section: Effect Of Formulation On Viability Of Caco-2 Cellsmentioning
confidence: 99%